Multiracial Campus Professionals' Experiences with Racial Authenticity. Issue 1 (2nd January 2019) - Harris, Jessica C.
ABSTRACT: Utilizing critical Multiracial theory, this study explores how Multiracial campus professionals' experiences with racial authenticity influence their work in postsecondary contexts. Three themes were generated from 24 Multiracial campus professionals' narratives, including encountering racial authenticity tests, navigating the authenticity trap, and Black Lives Matter and professionals' internalization of racial authenticity tests. This study explores how Multiracial professionals' experiences with racial authenticity often constrain their ability to foster inclusion and educational equity on campus and mediates their connections with students and colleagues.